新冠疫情下的印尼初级汉语学习者网络教学状况分析 - Nur Musyafak; Muhammad Aris Ichwanto (Universitas Negeri Malang, 2022)
Abstract: This research, based on reports published by Modern Language Association, analyzed enrollments in languages other than English in United States institutions of higher education from 2002 to 2016. Results show that American college students’ interest on foreign languages have been increasing unsteady since the 1950s, but the increasing rates kept low; and given the factors like the Great Depression since 2009, college students’ interests on foreign language and other disciplines of humanity have dropped abruptly. The enrollment of Chinese classes has reached its peak in 2013 but then experienced a 13 percent decrease. This study suggests, to promote Chinese education in the US, teachers should develop practical contents and encourage students to study advanced classes, and government of China should develop its soft power to attract more students to study Chinese. 摘要: 新冠肺炎病毒的突发事件影响了学校教学的很多方面。今年3月初印尼教育部部长提出新的教育政策，其中一个是各个教育单位要进行网络教学。不过，针对初级汉语学习者来说，通过网络学习第二语言教学的确具有一定的难度。本文通过调查问卷，考察了初级汉语学习者上网课的情况，并记录了网课的师生配合方式，查看学习者的学习过程、效果。根据这三个方面总结了初级汉语学习者线上教学特点和遇到的困难，提出了应对线上教学难题的策略，以期能更好地提高汉语网课的教学效果。